PENGAYAAN SENJATA NUKLIR SEBAGAI MODAL EKONOMI KOREA UTARA - Theofilus Jose Setiawan; Maria Sukmaniara; Jain Komboy; Darynaufal Mulyaman (Universitas Jenderal Ahmad Yani, 2021)
The purpose of the paper is to analyze North Korea's efforts to obtain economic capital through the enrichment of nuclear weapons amid the various sanctions imposed on it. This paper uses a constructivism approach in accordance in term of give arguments regarding North Korea's struggle to gain economic capital is an all-out struggle. Since the communist regime took control of North Korea, North and South Korea have continued to conflict to this day. Supported by the Soviet Union and aided by China during the Cold War era, North Korea was still able to survive. However, after the collapse of the Soviet Union and China's lack initiatives from helping North Korea, the North Korean economy worsened. In this paper, we found that North Korea used its nuclear capability as a bargaining chip to get what it wanted, especially for economic reasons.